Nrf2 Activation Attenuates Chronic Constriction Injury-Induced Neuropathic Pain via Induction of PGC-1α-Mediated Mitochondrial Biogenesis in the Spinal Cord. (21st October 2021) - Sun, Jia; Li, Jia-Yan; Zhang, Long-Qing; Li, Dan-Yang; Wu, Jia-Yi; Gao, Shao-Jie; Liu, Dai-Qiang; Zhou, Ya-Qun; Mei, Wei
Abstract : Background . Neuropathic pain is a debilitating disease with few effective treatments. Emerging evidence indicates the involvement of mitochondrial dysfunction and oxidative stress in neuropathic pain. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a potent regulator of the antioxidant response system. In this study, we investigated whether RTA-408 (RTA, a novel synthetic triterpenoid under clinical investigation) could activate Nrf2 and promote mitochondrial biogenesis (MB) to reverse neuropathic pain and the underlying mechanisms. Methods . Neuropathic pain was induced by chronic constriction injury (CCI) of the sciatic nerve. Pain behaviors were measured via the von Frey test and Hargreaves plantar test. The L4-6 spinal cord was collected to examine the activation of Nrf2 and MB. Results . RTA-408 treatment significantly reversed mechanical allodynia and thermal hyperalgesia in CCI mice in a dose-dependent manner. Furthermore, RTA-408 increased the activity of Nrf2 and significantly restored MB that was impaired in CCI mice in an Nrf2-dependent manner. Peroxisome proliferator-activated receptor-gamma coactivator-1alpha (PGC-1 α ) is the key regulator of MB. We found that the PGC-1 α activator also induced a potent analgesic effect in CCI mice. Moreover, the antinociceptive effect of RTA-408 was reversed by the preinjection of the PGC-1 α inhibitor. Conclusions . Nrf2 activation attenuates chronic constriction injury-induced neuropathic pain via induction of PGC-1 α -mediated mitochondrial biogenesis in the spinal cord. Our results indicate that Nrf2 may be a potential therapeutic strategy to ameliorate neuropathic pain and many other disorders with oxidative stress and mitochondrial dysfunction.